Hadith #3373 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Jabir ibn 'Abdullah; Sufyan bin 'Uyaynah سفيان بن عيينة; Sulaiman bin Atyq سليمان بن عتيق; Yahya bin Ma'in يحيى بن معين (Sunan Abi Dawud)
The Prophet (ﷺ) forbade the sale of fruits till they were clearly in good condition , and (ordered that) they should not be sold but for dinar or dirham except Araya.
Grade: Sahih

Hadith #4606 - Sunan Abi Dawud - al-Ahnaf bin Qays الأحنف بن قيس بن معاوية; Ibn Jurayj ابن جريج; ibn Mas'ud; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sulaiman bin Atyq سليمان بن عتيق; Tlq bin Habib al-Nzy al-Bsry طلق بن حبيب; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
If any one introduces into this affair of ours anything which does not belong to it, it is rejected. Ibn `Isa said: The Prophet (ﷺ) said: If anyone practices any action in a way other than our practice, it is rejected.
Grade: Sahih